The Role of Social Upbringing Institutions in Raising Awareness and Counseling about the Danger of Drugs, Khartoum, Sudan - Ali, Shaza Omer (Journal of Educational and Psychological Sciences, 2023)
The phenomenon of drug addiction has become a general phenomenon, and no society or group is free of it. Besides its appearance among the ranks of the youth who represent the workforce, and the producers in any society, it has appeared even among some of the younger generation, and it also appears among the poor and rich classes on Both. The reasons for the spread of this phenomenon have varied, according to the diversity of scholars' views on it, as psychologists believe that the spread of this phenomenon is due to the same person, while sociologists believe that society is the reason for the emergence of this scourge, while another team believes that drug addiction is A combination of several psychological, social, economic and political factors as well, The study aimed to identify the role of social upbringing institutions in raising awareness and counseling against the danger of addiction. The study used the inductive method. Hence the results of the study revealed the following: Not all families provide sufficient awareness and counseling for their children about the risk of addiction, due to the ignorance of many them of the foundations of awareness, counseling and the best upbringing methods. Moreover, there are no organized counseling programs in schools to illuminate students against the danger of addiction. In addition to the lack of the accompanying awareness programs that keeping pace with the size of the accelerated media development. Besides that, it does not provide the role of guidance, appropriate guidance, and the attractive method that helps in performing their role effectively, due to the necessity of integrating the roles of socialization institutions, that will lead to the better results in eliminating this phenomenon which destroys and decimates the society as a whole
Keywords: Social Upbringing; Psychological Counseling; Drugs